Stable properties under weakly geometrically flat maps - Barlet, Daniel; Magnússon, Jón (MATHEMATICA SCANDINAVICA, 2025)
In this note we show that a weakly geometrically flat map $π \colon M→ N$ between pure dimensional complex spaces has the local lifting property for cycles. From this result we also deduce that, under these hypotheses, several properties of $M$ are transferred to $N$.